High Levels of Recombination among Streptococcus pneumoniae Isolates from the Gambia - E. S. Donkor (American Society for Microbiology, 2011)
ABSTRACT We carried out multilocus sequence typing (MLST) on 148 pneumococcal carriage isolates collected from children <24 months old in the Upper River Division, the Gambia. MLST revealed a diverse population. Seventy-six different sequence types (STs) were found, the most common of which were 802 and 919, associated with 23F and 6A serotypes, respectively. Comparison with the MLST database showed that only 11 of the STs found in the present sample had been reported outside Africa. Six STs showed evidence of capsular switching (172, 802, 847, 1730, 1736, and 1737). Serotype switches were confirmed by microarrays that detected capsule genes. Of isolates analyzed by using microarrays, 40/69 (58%) harbored the tetM resistance determinant. A statistical genetic analysis to detect recombination found that 49/144 (34%) isolates showed significant (P < 0.05) evidence of admixture, which is greater than that observed in similar samples from the United Kingdom (5%) and Finland (2%). We hypothesize that large amounts of admixture could reflect the high prevalence of multiple carriage in this region, leading to more opportunities for homologous recombination between strains. This could have consequences for the population response to conjugate vaccination. IMPORTANCE The population structure of the pneumococcus in sub-Saharan Africa has barely been studied despite the high levels of morbidity and mortality due to pneumococcal disease in this region. We report the largest sample to date from carriage in sub-Saharan Africa to be typed by sequencing (multilocus sequence typing [MLST]) and microarray analysis. The results clearly show that the population is highly distinct and divergent from others studied in the United States and Europe. Moreover, in contrast with samples from developed countries, the population contains a high proportion of isolates showing a history of homologous recombination, which shuffles genetic information into new combinations and can generate drug-resistant and vaccine escape strains. This is likely to have important consequences for the evolutionary response of the pneumococcal population to conjugate vaccination targeting a subset of pneumococcal serotypes, which is under way in the Gambia and other countries.